2016
DOI: 10.1155/2016/2391476
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Modified Expanded Polystyrene Concrete after Dynamic Cyclic Loading

Abstract: EPS concrete was produced by mixing the expanded polystyrene spheres (EPS) and polymer emulsion and thickener to the matrix concrete, and this concrete had good vibration energy absorption characteristics. Based on the experimental data obtained on EPS volume ratio of 0%, 20%, 30%, and 40% by replacing matrix or coarse aggregate, the two design styles had nearly the same compressive strength. By applying frequency of 5 Hz, 50000 or 100000 times, 40 KN, 50 KN, and 60 KN cyclic loading, it is shown that the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
(16 reference statements)
2
12
0
1
Order By: Relevance
“…In addition all the observations made on the general aspect and the structure of the studied material, were also observed by San-Antonio-Gonzalezetal in his study led on a lightweight material made with gypsum and extruded polystyrene waste [7]. Wenbo and shi also showed that the expanded polystyrene particles adhere well to the cementitious matrix and even remained intact after the destruction of the samples [25].…”
Section: Sand Plastersupporting
confidence: 64%
“…In addition all the observations made on the general aspect and the structure of the studied material, were also observed by San-Antonio-Gonzalezetal in his study led on a lightweight material made with gypsum and extruded polystyrene waste [7]. Wenbo and shi also showed that the expanded polystyrene particles adhere well to the cementitious matrix and even remained intact after the destruction of the samples [25].…”
Section: Sand Plastersupporting
confidence: 64%
“…Wenbo Shi et al (8) Produced EPS concrete by mixing expanded polystyrene beads with polymer emulsion and add it to the concrete. EPS was added by volume ratio of 0%, 20%, 30%, and 40% by replacing the matrix or the gravel.…”
Section: Introductionmentioning
confidence: 99%
“…There was set a task to produce heat-insulating polystyrene concrete of B0,5-B1 classes with average densities of 250-800 kg/m3. Any calculated composition was corrected during the solar thermal treatment, taking into account the influence of temperature and the degree of dilution of the polystyrene-concrete mixture on the forming structure [2,3,4]. The dosage of the components of polystyrene concrete was carried out for cement by weight, for quartz sand by volume and weight, for polystyrene, water and additives by volume.…”
Section: Methodsmentioning
confidence: 99%